Development of mobile AR applications as a science learning media in increasing junior high school students’ interest in learning - Supardi, Supardi; Putra, Rezi Kuarta; Iqbal, Muhammad; Toni, Kornelius (PT The Collaboration UVW, 2023)
The solar system is a vast universe residing within a galaxy of galaxies consisting of celestial bodies circling a central solar system. Celestial bodies contained in the solar system consist of the moon, asteroids, meteoroids, comets, and planets this study carried out the development of planetary recognition applications with augmented reality technology. This application development uses marker-based tracking technology with the waterfall method. Based on the test results, the application can run on several smartphones that have different specifications. This application can be suitable to detect markers with room lights lighting 20 watts with a height of 10-40 cm.